Nepali Translation and Reliability Analysis of Quantitative Androgen Deficiency in the Aging Male Questionnaire - Risal, P.; Maharjan, A.; Bhatt, R. D.; Tamrakar, D. (Kathmandu University Medical Journal, 2020)
Background Androgen deficiency is diagnosed on the basis of clinical symptoms and laboratory assessment of testosterone level. Different screening tools have been developed to evaluate the sign and symptoms. Objective In this study, we examine the validity and reliability of the Nepali version of the quantitative Androgen Deficiency in Aging Male (qADAM) questionnaire to screen androgen deficiency in Nepali male. Method English dialectal quantitative Androgen Deficiency in Aging Male questionnaire was forward translated to Nepali version and backward translated. This version was reviewed by a panel of an endocrinologist, a clinical psychiatrist, a physician, and a clinical biochemist. A final Nepali version of qADAM was developed. Thirty-one healthy male aged 31-70 years were administered with the questionnaire in two separate occasions two weeks apart. Cronbach’s alpha and test-retest reliability were calculated to identify validity and reliability, respectively. Result In the Nepali translated questionnaire, Cronbach’s alpha for internal consistency from ten items is good (0.68). The Cronbach’s alpha for internal consistency from nine items without item 7 is 0.706. Seven out of ten items had an R-value of > 0.7. In the total sample, Standard Error Mean (SEM) ranged from 0.00-0.44 for qADAM. SEM% are low for all variables (0.00-11.20%). MDC95 ranged 0.00-1.234. MDC95% ranged 0.00 – 31.05% and was < 30% for majority of variables (90%). Conclusion The final translated Nepali questionnaire seems reliable and valid. A future study measuring the Nepali questionnaire with testosterone level and another biochemical test in control and androgen deficiency patients will help validate the questionnaire.